Devolution of natural resource management - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
From fishers in the Philippines to pastoralists in Morocco and rubber tappers in the Amazon, local communities have been actively participating in the management of natural resources. Since the 1990s, there has been a growing recognition of the benefits that can be derived from transferring control over natural resources from central governments to local bodies. At the international level, this trend is seen in agreements such as the Convention to Combat Desertification and the Convention on Biological Diversity that commit signatories to principles of decentralization, subsidiarity, and local participation. At the national level, many countries in Africa, the Americas, Asia, and Europe have devolved management responsibilities over rangelands, forests, fisheries, and irrigation to local government authorities, resource users, or both.